Persepsi Masyarakat Kelurahan Rungkut Kidul terhadap Layanan Kelas Parenting Puspaga Balai Rw - Alfianti, Garneza Merlyana; Endik Hidayat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Cases of violence against women and children are a public problem that must be answered by the government. The Surabaya City Government together with DP3APPKB Surabaya in 2017 formed the PUSPAGA program with a service center on Floor II of the former Siola Building and in 2022 it developed into PUSPAGA Balai RW with a program for prevention, risk reduction and handling of cases related to families, women and children. One of the services of the prevention program by PUSPAGA Balai RW is Parenting Classes. In implementing parenting classes there are several challenges, such as in Rungkut Kidul Village where there are still few participants attending parenting classes. So the target of this parenting class has not been achieved. This research aims to describe the perceptions of the people of Rungkut Kidul Subdistrict regarding the PUSPAGA Balai RW parenting class services. The research method used is a qualitative descriptive method with data collection techniques through interviews, observation and literature studies that are relevant to this research. The results of the research show that the perception of the Rungkut Kidul Village Community consists of 60% agreeing and 40% disagreeing with the existence of Parenting Class services. These results are deepened by public perceptions based on the 5 attributes of public service innovation according to Rogers which shows that parenting class services implemented in Rungkut Kidul Subdistrict have relative advantages, suitability, complexity and are not easy to try and easy to observe. (10pt, single line spacing, Palatino Linotype font).